2020
DOI: 10.1155/2020/8822361
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-31-5p Exacerbates Lipopolysaccharide-Induced Acute Lung Injury via Inactivating Cab39/AMPKα Pathway

Abstract: Acute lung injury (ALI) and the subsequent acute respiratory distress syndrome remain devastating diseases with high mortality rates and poor prognoses among patients in intensive care units. The present study is aimed at investigating the role and underlying mechanisms of microRNA-31-5p (miR-31-5p) on lipopolysaccharide- (LPS-) induced ALI. Mice were pretreated with miR-31-5p agomir, antagomir, and their negative controls at indicated doses for 3 consecutive days, and then they received a single intratracheal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 49 publications
0
38
0
Order By: Relevance
“…Our previous work demonstrated that salivary IL-6 is a highly sensitive biomarker of OSCC; thus, we find it significant that both IL-6 and miR-31 are known to contribute to cancer stem cell maintenance in different tumor types [57][58][59][60]. In addition, IL-6 and miR-31 expression are closely co-regulated: IL-6 was shown to activate the Hippo pathway and to upregulate miR-31-5p, resulting in experimental cancer in mice [61]; at the same time, downregulation of miR-31-5p attenuated IL-6 production and release in LPS-induced murine acute lung injury [62].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work demonstrated that salivary IL-6 is a highly sensitive biomarker of OSCC; thus, we find it significant that both IL-6 and miR-31 are known to contribute to cancer stem cell maintenance in different tumor types [57][58][59][60]. In addition, IL-6 and miR-31 expression are closely co-regulated: IL-6 was shown to activate the Hippo pathway and to upregulate miR-31-5p, resulting in experimental cancer in mice [61]; at the same time, downregulation of miR-31-5p attenuated IL-6 production and release in LPS-induced murine acute lung injury [62].…”
Section: Discussionmentioning
confidence: 99%
“…Although we were unable to demonstrate that poly(I:C) preconditioning significantly altered MSC-EV miRNA content, it is likely that EV-mediated transfer of miRNAs released from MSCs in the presence or absence of poly(I:C) stimulation may influence innate immunity via regulation of proinflammatory and anti-inflammatory cytokine production and antimicrobial responses ( Bulut and GÜrsel, 2020 ). Several of the identified abundant EV miRNAs have been shown to act as regulators of immune and inflammatory responses including miR-21-5p, let-7f, miR-199a, miR-221, miR-423-5p, miR-409-3p, miR-181a-5p, miR-22, miR-100-5p, miR-30a-5p, and miR-31-5p ( Sheedy, 2015 ; Qian et al, 2016 ; Wan et al, 2016 ; Zhu et al, 2017 ; Liu et al, 2019 ; Luo et al, 2019 ; Wang et al, 2019 ; Jiang et al, 2020 ; Li et al, 2021 ). Analysis of predicted gene targets of these highly expressed miRNAs identified several signaling pathways important in innate immunity including the MAPK signaling pathway, PI3K-Akt signaling pathway, chemokine signaling pathway, transforming growth factor beta signaling pathway, and the TLR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is a multifunctional kinase with anti-inflammatory and antioxidant capacities that has already been identified as a strategic cellular target to treat ALI ( 7 , 17 , 19 ). AC works downstream of G protein-coupled receptors and is essential for the rapid induction of intracellular cAMP synthesis, which ultimately causes PKA activation ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (18) previously found that AMPK activation attenuated nuclear factor-κB (NF-κB) transcription miR-351-5p aggravates lipopolysaccharide-induced acute lung injury via inhibiting AMPK activity via increasing TANK-binding kinase 1 phosphorylation, thereby preventing adipose tissue inflammation. AMPK also suppressed NLRP3 inflammasome activation and alleviated lipopolysaccharide (LPS)-induced ALI in mice (7,19). Nuclear factor erythroid-2 related factor 2 (NRF2) functions as a redox-sensitive transcription factor and is required for the synthesis of various antioxidant enzymes, including superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (gPx) (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%